2001
DOI: 10.1116/1.1349202
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the electron field emission from carbon nanotubes

Abstract: Using a tunneling approach for the field emission from a single carbon nanotube, expressions for the emission current as a function of the anode voltage and of the emitted electron energy spectrum are obtained. The low dimensionality of the electronic system of a carbon nanotube is taken into account. The extraction field on the nanotube’s tip is evaluated using numerical computations. For nanotubes of practical interest, having large enough diameters, it is demonstrated that the influence of the detailed form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…For a single, isolated CNT, the value of enhancement factor is believed to be dependant on the length, radius, and type of structure, i.e., multiwalled ͑MWNT͒, singlewalled ͑SWNT͒, open or closed cap: This has been subject to several computational and experimental investigations. [3][4][5][6][7][8] Geometric enhancement is not just applicable to CNT but also exists in a number of other tip-based structures including: SiC nanowires, 9 MoO 3 nanobelts, 10 tungsten nanowires, 11 spindt tips, 12 and copper sulphide nanowire arrays. 13 Much of the analysis performed on experimental data has relied upon analysis of the emission current I to field E ͑or voltage V͒ characteristics using the wellknown field emission mechanism of Fowler and Nordheim.…”
mentioning
confidence: 99%
“…For a single, isolated CNT, the value of enhancement factor is believed to be dependant on the length, radius, and type of structure, i.e., multiwalled ͑MWNT͒, singlewalled ͑SWNT͒, open or closed cap: This has been subject to several computational and experimental investigations. [3][4][5][6][7][8] Geometric enhancement is not just applicable to CNT but also exists in a number of other tip-based structures including: SiC nanowires, 9 MoO 3 nanobelts, 10 tungsten nanowires, 11 spindt tips, 12 and copper sulphide nanowire arrays. 13 Much of the analysis performed on experimental data has relied upon analysis of the emission current I to field E ͑or voltage V͒ characteristics using the wellknown field emission mechanism of Fowler and Nordheim.…”
mentioning
confidence: 99%
“…For instance, it has been attributed to the curvature of the apex [82]; to small size and strong local fields that lead to localized states at the apex [20,59,83]; to the space charge vs thermionic emission [15,60]; to the adsorbate effects [21]; to the back contact resistance [84]; and so on. The emission current from CNTs have been estimated by taking into account the band structures of CNTs [47,48,49]. It is found that current depends on the chirality only at very high temperatures [49].…”
Section: The Fowler-nordheim Theorymentioning
confidence: 99%
“…The SWCNT can either be metallic or semiconducting. The field emission properties have been calculated by the tight-binding theory and scattering theory [47,48,49]. In recent years, quantum mechanical simulations of the field emission of CNTs have been performed [50,51,52,53,54,55].…”
Section: Introductionmentioning
confidence: 99%
“…4 However, in this study the potential all around the emitting CNT tip has been assigned a constant value equal to an average local field, an approximation, the effects of which are still not clear to us. In another approach Filip et al 5,6 have modelled emission from CNTs with large radii but have still used a one-dimensional transmission coefficient of the Fowler-Nordheim type. In this paper we calculate the transmission coefficient as a function of the angle to the axis of the tube and of the energy.…”
Section: Introductionmentioning
confidence: 99%